Reasons and impacts of alcohol use disorder among ethnic minority young adults: a descriptive phenomenological study - Belay, Getaneh Mulualem; Wah, Mak Yim; Lam, Katherine Ka Wai; Liu, Qi; Ting, Mao; Xi, Chen; Yang, Funa; Wu, Cynthia Sau Ting; Ho, Ka Yan (Frontiers in Public Health, 2025)
IntroductionAlcohol use disorder (AUD) is prevalent among ethnic minority young adults. However, there is limited evidence exploring its health impact and contributing factors in ethnically marginalized young adults. Therefore, this study examined the reasons for developing AUD and its effect on the daily lives of ethnic minority young adults.MethodA descriptive phenomenological study was conducted from March 1 to June 30, 2023. Participants were recruited through referral using the exponential snowball sampling technique. A total of 22 ethnic minority young adults were interviewed using a semi-structured interview guide. The sample size was determined based on data saturation. All interviews were audio-recorded and transcribed verbatim in English. Then, the data was analyzed using Colaizzi’s method.ResultsThis study suggested that the reasons for developing AUD among ethnic minority young adults were (1) culture and family, (2) hedonistic motives, (3) curiosity, (4) low-risk perception, (5) coping motives, (6) social influences, and (7) subjective cravings. Moreover, this study indicated that ineffective daily performance, emotional turmoil, financial constraints, and social relationship issues were the impacts of AUD on this segment of the population.ConclusionThe findings highlighted the multifaceted reasons contributing to AUD among ethnic minority young adults, including coping, low-risk perception, and influences from culture, family, and peers. The findings also showed how AUD severely affected their daily lives. Therefore, future interventional studies should consider cultural, family, social, and psychological aspects.